The enigmatic SLC26A6 multifunctional anion transporter: recent advances in structure-function relationship, pathophysiological significance and novel pharmacological inhibitors - Seidler, Ursula E. (Frontiers in Pharmacology, 2025)
SLC26A6, a member of the SLC26 family of multifunctional anion transporters, has been particularly enigmatic because of its multiple modes of transport, its expression in organs that are difficult to study physiologically, and the lack of specific antibodies and inhibitors. This has recently changed. SLC26A6 is expressed in the human pancreas, kidney, intestine, heart and some other organs and is involved in fluid absorption, anion secretion, regulation of intracellular pH and elimination of waste products such as oxalate. This review will focus on three topics: Firstly, a molecular structure of human SLC26A6 has recently been obtained by cryo-electron microscopy. Structure-function studies of the reconstituted SLC26A6 in proteoliposomes suggested a 1:1 stoichiometry, resulting in electroneutral Cl−/HCO3− exchange and electrogenic Cl−/oxalate2− exchange. How do these data help to understand the published functional studies? Secondly, whole exon sequencing of a kidney stone cohort from the United Kingdom database revealed a dominant negative SLC26A6 mutation in a patient with enteric hyperoxaluria, oxalate kidney stones and a low calcium diet. How does this finding fit with previous genetic studies in mice and humans of SLC26A6 gene mutations? Thirdly, progress has been made in identifying specific inhibitors for SLC26A6. Where might this be of clinical relevance?